Interleukin-6 in the central amygdala is bioactive and co-localised with glucagon-like peptide-1 receptor - Anesten Fredrik; Gasull Adrià Dalmau; Richard Jennifer E; Farkas Imre; Mishra Devesh; Taing Lilly; Zhang Fuping; Poutanen Matti; Palsdottir Vilborg; Liposits Zsolt; Skibicka Karolina P; Jansson John-Olov (WILEY, 2022)
Neuronal circuits involving the central amygdala (CeA) are gaining prominence as important centres for regulation of metabolic functions. As a part of the subcortical food motivation circuitry, CeA is associated with food motivation and hunger. We have previously shown that interleukin (IL)-6 can act as a downstream mediator of the metabolic effects of glucagon-like peptide-1 (GLP-1) receptor (R) stimulation in the brain, although the sites of these effects are largely unknown. In the present study, we used the newly generated and validated RedIL6 reporter mouse strain to investigate the presence of IL-6 in the CeA, as well as possible interactions between IL-6 and GLP-1 in this nucleus. IL-6 was present in the CeA, mostly in cells in the medial and lateral parts of this structure, and a majority of IL-6-containing cells also co-expressed GLP-1R. Triple staining showed GLP-1 containing fibres co-staining with synaptophysin close to or overlapping with IL-6 containing cells. GLP-1R stimulation enhanced IL-6 mRNA levels. IL-6 receptor-alpha (IL-6R alpha) was found to a large part in neuronal CeA cells. Using electrophysiology, we determined that cells with neuronal properties in the CeA could be rapidly stimulated by IL-6 administration in vitro. Moreover, microinjections of IL-6 into the CeA could slightly reduce food intake in vivo in overnight fasted rats. In conclusion, IL-6 containing cells in the CeA express GLP-1R, are close to GLP-1-containing synapses, and demonstrate increased IL-6 mRNA in response to GLP-1R agonist treatment. IL-6, in turn, exerts biological effects in the CeA, possibly via IL-6R alpha present in this nucleus.